DO INTELLECTUAL CAPITAL AND INTANGIBLE ASSETS INFLUENCE THE FIRM VALUE? (CASE STUDY IN TRADE, SERVICE, AND INVESTMENT SECTOR IN INDONESIA) - Giovanni Giovanni; Setyarini Santosa (Universitas Multimedia Nusantara, 2020)
The objective of this research is to examine the influence of intellectual capital and intangible assets toward firm value. The use of intellectual capital and intangible assets in this research is very interesting because they represent the similar idea, the ability to generate future benefit. However, intellectual capital is not represented in the presentation of financial statement directly, while the intangible asset is presented in the financial statement. The samples are taken from the trade, service, and investment companies classification which are listed in Indonesia Stock Exchange in from 2015 until 2018. Using the purposive sampling, there are 27 companies put as data for the multiple linear regression. The result of the research shows intellectual capital has positive significant relationship toward firm value, meanwhileintangible assets have negative significant relationship toward firm value. It means the lower intangible assets, the higher firm value is. This might be happened if the company cannot utilize the intangible asset optimally.